Perancangan Sistem Informasi Perpustakaan SMA Negeri 1 Gombong Berbasis Web Menggunakan Hypertext Preprocessor (PHP) dan MySQL - Putra, Adam Nusa; Muflih, Ghufron Zaida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
PHP is a popular open-source programming language widely used in web application development due to its ease of learning, the availability of numerous libraries, and its ability to integrate with MySQL databases. This study aims to design and develop a library information system that can enhance the efficiency of school library management. The methodology employed in this research is the Waterfall method, which consists of the stages of requirements analysis, system design, implementation, and testing. In the requirements analysis stage, user needs are identified, and the key features that must be included in the system are determined, such as book search, borrowing and returning books, and managing library member data. The design stage involves creating system models and database designs that support the integration and efficiency of library data management. The implementation is carried out by developing the system using PHP as the programming language and MySQL as the database management system. The result of this research is a responsive and user-friendly web-based library information system application, specifically designed to meet the needs of the SMA N 1 Gombong library. This application provides essential features such as book search, book borrowing and returning management, and library member data management. Additionally, the system is designed with an intuitive interface, making it easy for users to operate. Based on the testing and evaluation results, it can be concluded that this web-based library information system significantly contributes to improving the efficiency of library data management. By utilizing PHP and MySQL, this application has proven to be an effective and efficient technological solution to support library operations at SMA N 1 Gombong